Successful weight loss maintenance: A systematic review of weight control registries - Paixão, Catarina (2020)
Weight loss maintenance is a major challenge for obesity treatment. Weight control registries can be useful in identifying psychological and behavioural factors that could contribute to better long-term success. The objective of this study is to describe the existing weight control registries and their participants and identify correlates of weight loss maintenance. A comprehensive search of peer-reviewed articles published until November 2018 was conducted in PubMed, Web of Science, and Scopus. Studies that reported results from weight control registries were considered. Fifty-two articles, corresponding to five registries (the United States, Portugal, Germany, Finland, and Greece), were included. Registries differed in inclusion criteria and procedures. Of 51 identified weight loss and maintenance strategies, grouped in 14 domains of the Oxford Food and Activity Behaviors taxonomy, the following were the most frequently reported: having healthy foods available at home, regular breakfast intake, increasing vegetable consumption, decreasing sugary and fatty foods, limiting certain foods, and reducing fat in meals. Increased physical activity was the most consistent positive correlate of weight loss maintenance. To our knowledge, this is the first systematic review of information about successful weight loss maintenance obtained from weight control registries. Key common influential characteristics of success were identified, which can inform future prospective studies and weight management initiatives.